Punishment and Public Reason: Reply to Hoskins. Issue 1 (2nd January 2023) - Flanders, Chad
Abstract : In his paper "Public Reason and the Justification of Punishment, " Zachary Hoskins develops and defends an idea of "public reason" that might be applicable to debates over punishment in the Western world. This short reply takes issue with some of Hoskins' conclusions (while agreeing with many of his premises), and suggests that contra Hoskins, many versions of retribution are not compatible with the ideal of public reason as Rawls articulated it. Instead, debates over criminal justice and punishment should properly revolve around the goods of public safety and harm reduction—rather than around any of the supposed metaphysical goods achieved by retributive punishment.